EXPLORATION OF FOOD GREEN PRODUCT INDICATORS IN INDONESIA: STUDIES ON RESPONDENTS HAVING USED FOOD GREEN PRODUCTS - Asep Rokhyadi Permana Saputra; Subarjo Subarjo; Raswan Udjang; Fety Rochyawati Qudrat Mulya (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The need for green products or green products is increasing, including food products. Along with the existence of global warming which results in vigilance for humans. The existence of green products currently still creates a paradigm confusion for the consensus. Consumer distrust, low knowledge, past experience, fluctuating income, cause confusion for consumers to consume green products. This research aims to find out how far the respondents of green product users are towards their perception of green products themselves. This research aims to find out how far the respondents of green product users are towards their perception of green products themselves.This research is an action research that explores the attitudes or perceptions of respondents who have used green products. Sample uses actidental sampling for 600 respondents in 6 provinces on Java island, namely Banten, DKI Jakarta, West Java, Central Java, East Java, and DI Yogyakarta. The analytical tool used is structural equation modeling with AMOS. All of the indicator of the green product are significant, except quality to has a tastier taste, green product to environment product, and green product to label of product, but the other indicators show that has significant, they are green product to safety, green product to price, green product to quality, green product to past experience, green product to healthy, safety to safer for animal, safety to free from added chemical substances, safety to free from genetic engineering, price to price according to the quality obtained, price to prices are more expensive than conventional foods, quality to have a higher level of freshness, environment product to better for environmental sustainability, past experience to rely on past experience rather than information about labels, health to maintain and increase endurance, health to has more nutritional content, label product to easy to read, and label product to accurate label. This indicates that the respondents did choose green products because of the needs of those who are aware of products that are healthy and environmentally friendly.